Modeling Household Energy Use in the Czech Republic - Cortez, Danica (2020)
Energy statistics in the realm of national statistics have become increasingly important. The demand for capturing these statistics on the part of international organizations, specifically Eurostat, has equally increased. This paper presents an exploration of energy estimation models that can be utilized for estimating total energy consumption on the national and household level. The first part covers the theoretical framework that has been built by researchers over the past decades with regards to modeling household energy consumption. Next, a brief overview is given on how energy statistics are produced in Europe and in the Czech Republic, including the common methods of producing household energy consumption statistics. Next, an analysis is offered on the energy consumption in the Czech Republic, including its evolution through time as well as its breakdown over different sectors. Finally, a presentation of models is given, along with their estimates and forecasts. This report found that regional differences in energy consumption exist, as well as stark differences between dwelling types and region density. In the Czech Republic, dwellings that are household consume more energy than apartments. The upper estimates for energy consumptions for households suggest an increase between 11% to 17% from 2019 to 2029. The upper estimates for national consumption for the Czech Republic predict an increase of between 1.89 to 1.99 exajoules by 2029.